Dr. Don Edward Walicek and Prof. Dr. Susanne Mühleisen on language practices of West African and the English on the Gold Coast during colonial times - Walicek, Don Edward; Mühleisen, Susanne (Cluster Conversations, 2024)
In this episode, Cluster fellow Prof. Dr. Don Edward Walicek (University of Puerto Rico) talks with his host Prof. Dr. Susanne Mühleisen (University of Bayreuth) about Walicek's research project “Language Ideologies and Social Contact Involving West Africans and the English on the Gold Coast.” In this project, Walicek examines dynamics of linguistic contact among Europeans and West Africans who were involved in or otherwise impacted by the Atlantic slave trade. Focusing on language ideologies, it pays special attention to the English presence on the Gold Coast during the 16th and 17th centuries (1553-1700) given that the region was a major source of people sold into slavery as well as a point from which many departed for the Caribbean. The analyzed materials consist of documents that have not been fully examined by linguists, such as local correspondence of the Royal African Company of England.